2014
DOI: 10.3109/10428194.2014.955020
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric sensitivity and characteristics of plasma cells in patients with multiple myeloma or its precursor disease: influence of biopsy site and anticoagulation method

Abstract: Flow cytometry has increasing relevance for prognosis in myeloma and precursor disease (monoclonal gammopathy of unknown significance/smoldering myeloma), yet it has been reported that plasma cell enumeration by flow varies depending on the quality of marrow aspirate and field biopsied in patchy disease. We demonstrated increased sensitivity of flow over immunohistochemistry in abnormal-plasma cell detection in monoclonal gammopathy (n = 59)/smoldering myeloma (n = 87). We prospectively evaluated treatment-naï… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 43 publications
6
15
1
Order By: Relevance
“…It is commonly recognized that BMPC are vastly underrepresented by flow cytometry [4,[27][28][29][30][31]. We also found that flow cytometry yielded significantly lower amounts of BMPC compared with smear morphology, which further confirms that it is the least reliable method to discriminate between plasma cell myeloma and MGUS.…”
Section: Discussionsupporting
confidence: 74%
“…It is commonly recognized that BMPC are vastly underrepresented by flow cytometry [4,[27][28][29][30][31]. We also found that flow cytometry yielded significantly lower amounts of BMPC compared with smear morphology, which further confirms that it is the least reliable method to discriminate between plasma cell myeloma and MGUS.…”
Section: Discussionsupporting
confidence: 74%
“…Recently, Manasanch et al . documented roughly a 50% morphologic decrease in second‐pull compared with first‐pull aspirates. These authors also documented that EDTA anticoagulation was associated with decreased viability in first‐pull aspirates compared with heparin, suggesting that first‐pull, heparin‐anticoagulated aspirates are the bone marrow specimen of choice for the flow cytometric evaluation of myeloma.…”
Section: Discussionmentioning
confidence: 97%
“…Notably, almost 1/3 of the FC results were reported to have significant hemodilution that can impact the accuracy of MRD detection. 23 The majority of discrepancies were noted between BM biopsy and FC reports. Importantly, 14/49 discrepant cases identified to be in a com- can vary dramatically between modalities tested.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate that disease detection discordance in the relapsed/refractory setting occurs more frequently than has been previously reported and was seen in approximately 15% of BM cases evaluated and approximately one‐third of all patients evaluated. Notably, almost 1/3 of the FC results were reported to have significant hemodilution that can impact the accuracy of MRD detection . The majority of discrepancies were noted between BM biopsy and FC reports.…”
Section: Discussionmentioning
confidence: 99%